Konsep Childfree dalam Perspektif Fiqih Kontemporer: Analisis Hukum, Etika, dan Maqashid Syariah - Zahro, Sholihah Fatimatuz; Isroqunnajah, Isroqunnajah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines the concept of childfree from the perspective of contemporary Islamic jurisprudence by analyzing its legal, ethical, and maqasid al-shariah dimensions. The research aims to explore how Islamic law responds to modern reproductive choices, particularly the decision of married couples not to have children permanently or temporarily. Using a qualitative method through library research, data were collected from classical and contemporary fiqh literature, journals, books, and relevant academic sources. The findings show that although classical Islamic scholarship does not address childfree directly, discussions on ‘azl serve as a foundational reference for reproductive regulation. Contemporary scholars extend this discourse by assessing the motives, impacts, and maslahah of childfree decisions. From an ethical standpoint, childfree is permissible when based on mutual agreement, responsibility, and the avoidance of harm. Through the lens of maqasid al-shariah, childfree may be justified if it aims to protect life, mental health, economic stability, or prevent harm to potential offspring. The study concludes that Islam neither mandates nor prohibits having children, and the permissibility of childfree depends on clear, responsible considerations aligned with family welfare and Islamic ethical principles. Keywords: Childfree, Contemporary Fiqh, Maqasid Shariah